Landnutzungswandel im westlichen Vorortsbereich von Tokyo - Sasaki, Hiroshi (ERDKUNDE, 1980)
This study demonstrates, including characteristics that are not described in greater detail here, that: (1) the metropolitan region of Tokyo shows an excessive decrease of green areas, particularly in districts of about 20 km distance from the centre of Tokyo and in the western suburbs. (2) Land utilisation in the western suburban zones of a spatial radius between 25 and 50 km has undergone a great change: from shrub forest and mulberry fields over other diverse unirrigated cultivation to an increasingly concentrating utilisation for residential and settlement land. (3) Urbanisation occurred along the axis of the Chuo rail way line, which serves the western suburban region; its stations developed into centres of smaller and larger suburbs, a fact which is underlined by the considerable increase in property prices proportional to their distance to a station. (4) The preferred direction of urbanisation was the west, especially the Musashino Upland, the attraction of which may be caused in part by the romantic element in Doppo Kunikida's narrative Musashino. (5) The few remaining agricultural enterprises have been completely absorbed in the process of urbanisation and are mainly conducted on a part-time basis. (6) The suburban towns of the metropolitan region of Tokyo are primarily dormitory towns with complementary functions in the field of industry, culture and leisure.